The Effect Of Ownership Structure On Profit Management Practice - نصار باسل; نعيسه راما (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to demonstrate the effect of ownership structure of Syrian joint-stock companies listed on the Damascus Stock Exchange in the practice of profit management. To achieve this goal, the researcher measured the ownership structure through two variables: managerial ownership measured by the ownership percentage of the members of the board of directors, and ownership concentration measured by the percentage of ownership of the major shareholders, Profit management was measured using the modified Jones model, which has been shown to be the best models of profit management measured. This study was conducted on all the shareholding companies listed on the Damascus Stock Exchange - except for the financial companies (banks) - which number (13) companies belonging to different sectors during the period between 2011-2018. The results showed that the Syrian shareholding companies listed on the Damascus Stock Exchange practiced profit management by rate 63%, which is a high percentage. The results also showed that there was no effect of the level of managerial ownership and the level of ownership concentration in the degree of profit management practice. Some recommendations were proposed to limit the practice of profit management in the Syrian shareholding companies listed on the Damascus Stock Exchange.